Oceanic Internal Waves and Internal Tides in the East Asian Marginal Seas - Nam, SungHyun; Chen, Xueen (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Oceanic internal waves (IWs) at frequencies from local inertial (e.g., near-inertial internal waves) to buoyancy frequencies (nonlinear internal waves or internal solitary waves), sometimes including diurnal and semidiurnal tidal frequencies, play an important role in redistributing heat, momentum, materials, and energy via turbulent mixing. IWs are found ubiquitously in many seas, including East Asian marginal seas (Indonesian Seas, South China Sea, East China Sea, Yellow Sea, and East Sea or Japan Sea), significantly affecting underwater acoustics, coastal and offshore engineering, submarine navigation, biological productivity, and the local and global climate. Despite decades of study on the IWs in some regions, our understanding of the IWs in the East Asian marginal seas is still in a primitive state and the mechanisms underlying every stage (generation, propagation, evolution, and dissipation) of IWs are not always clear. This Special Issue includes papers related to all fields of both low- and high-frequency IW studies in the specified region, including remote sensing, in situ observations, theories, and numerical models.